STUDI POLARISASI FLUORESENSI MENGGUNAKAN SAMPEL MINYAK SAWIT - Aziel Nimrod Febriyanto; Ketut Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
This study was conducted to compare the changes in fluorescence polarization angle for fresh cooking palm oil, expired or used cooking oils with electrooptic method. The samples are one brands with a variety of palm cooking oil expired, two fresh palm cooking oil samples and two samples of used cooking oil. Used a green laser with a wavelength of 532 nm as light source. The results showed that most small changes in polarization angle experienced by the samples of fresh oil then becomes greater for expired and used cooking oil samples. The biggest polarization angle changes occur in used cooking oils and oil expired that shows the low quality of the sample. The results showed that the polarization by fluorescence is possible to be used as a complementary test oil quality parameter.